National Contingents in United Nations Peace-Keeping Forces - Siekmann, Robert C.R. (Human Rights and Humanitarian Law - Book Archive pre-2000, 1991)
Are member states obliged to provide troops for United Nations peace-keeping operations? What criteria apply for the composition of UN forces? Does the host state have any say in this respect? And may national contingents be withdrawn at any time? Who pays the cost of participation? How are criminal trials of military personnel organized and what is their status? What influence do troop-contributing states have in the operational phase with regard to their own contingent and their members? This book sets out to answer these and many other relevant questions, examining operational practice in detail and assessing the results according to international law criteria. With the growing role of UN peace-keeping forces, Siekmann has produced an essential handbook for diplomats, legal advisers and the military.